Evaluation the Application of Asian Licensing Laws in Iraqi Soccer Primer - Abu baker Yousif Mohammed; Mushreq Khalil Fathi (College of Physical Education and Sport Sciences, 2021)
The research aimed at applying scale for identifying the reality of Asian licensing laws from the Iraqi soccer primer administrative board point of view as well as evaluating the application of these laws. The researchers used the descriptive method on the administrative board of the Iraqi soccer primer league. The data was collected and treated using proper statistical operations to conclude that the scale is standardized to reflect the reality of the Asian licensing list from the administrative board point of view. The results also showed that licensing is applied very well yet not good enough to get a fast, direct license. Finally, the researchers recommended the necessity of using this scale by the administrative board of the Iraqi federation to identify the level of sport administration according to the Asian licensing system to uplift the levels of Iraqi clubs to participate locally and internationally.